ANALISIS PENGARUH DIGITAL MARKETING UNTUK MENINGKATKAN USER ENGAGEMENT PADA UMKM TOKO ASRI DI KOTA MABA - Rongasala, Almeisya; Wahyono, Teguh (JURNAL LENTERA BISNIS, 2026)
This study aims to analyse the effect of digital marketing via TikTok on user engagement at the Toko Asri SME in Maba City. This study employs a quantitative approach using a survey method involving 97 respondents who are customers and TikTok users. The data were analysed using simple linear regression with the aid of SPSS. The results indicate that digital marketing has a positive and significant effect on user engagement, with a t-value of 13.228 and a significance level of <0.05. Furthermore, the coefficient of determination (R²) of 0.648 indicates that digital marketing accounts for 64.8% of the variation in user engagement. These results indicate that the use of TikTok as a digital marketing medium can increase user engagement with content presented by SMEs.